Thoracoscopic resection of a bronchogenic cyst in a 17-year-old girl - Pułtorak, Roksana; Korlacki, Wojciech; Pasierbek, Michał; Grabowski, Andrzej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Bronchogenic cysts comprise approximately 6% of mediastinal tumors in children. The treatment consists in surgical resection of the cyst. The authors present the case of a 17-year-old girl who was accidentally diagnosed with a mediastinal cyst. The patient was successfully treated with thoracoscopic surgery with good early and late clinical outcomes.